Development and validation of a novel epigenetic signature for predicting prognosis in colon cancer - Luo, Dakui; Liu, Qi; Shan, Zezhi; Cai, Sanjun; Li, Qingguo; Li, Xinxiang (Journal of cellular physiology, 2020)
Epigenetic factors play a critical role in carcinogenesis by imparting a distinct feature to the chromatin architecture. The present study aimed to develop a novel epigenetic signature for evaluating the relapse‐free survival of colon cancer patients. Public microarray datasets were acquired from the Gene Expression Omnibus databases: GSE39582, GSE17538, GSE33113, and GSE37892 set. Patients from GSE39582 set were randomized 1:1 into training and internal validation series. Patients were divided into high‐risk and low‐risk groups in training series based on a set of 11 epigenetic factors (p < .001). The good reproducibility for the prognostic value of the epigenetic signature was confirmed in the internal validation series (p < .001), external validation series (a combination of GSE17538 set, GSE33113 set, and GSE37892 set; p = .018), and entire series (p < .001). Furthermore, a nomogram, which integrated the epigenetic signature, pathological stage, and postoperative chemotherapy, was developed based on the GSE39582 set. The time‐dependent receiver operating characteristic curve at 1 year demonstrated that the comprehensive signature presented superior prognostic value than the pathological stage. In conclusion, an epigenetic signature, which could be utilized to divide colon cancer patients into two groups with significantly different risk of relapse, was established. This biomarker would aid in identifying patients who require an intensive follow‐up and aggressive therapeutic intervention. The present study aimed to develop a novel epigenetic signature for evaluating the relapse‐free survival of colon cancer patients. This biomarker would aid in identifying patients who require an intensive follow‐up and aggressive therapeutic intervention.